Răspuns:
Explicație pas cu pas:
a) f:R->R, f(x) =-8x²+x-12
f'(x)=-16x+1
b) f:IR -> IR , f(x) = 3x⁵+ 7 ^x
f'(x)=15x+7^x ·ln7
c) f:IR -> IR , f(x) = 2 e ^ x + 2 ^x - 4 ^x
f'(x)=2e^x+2^x×ln2-4^x×ln4
d) f:IR\{0} -> IR , f(x) = 3x ^7 + 1 /x ² - 1 / x^4
f'(x)=3x^7×ln3×7x^6+1/x^4·2x-1/x^8×4x=21x^13×ln3+2/x³-4/x^7
j) f:IR -> IR , f(x) = -3sinx + 2cosx
f'(x)=-3cosx-2sinx
h) f: ( 0 , plus infinit ) -> IR , f(x) = xIn7+2Inx
f'(x)=ln7+2/x
k) f:IR -> IR , f( x) = ( 3x+4 ) cos x
f'(x)=3 cosx-(3x+4) sin x
postaeza restul inca o data, merci